2000
DOI: 10.1038/35021074
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Mycobacterium tuberculosis in macrophages and mice requires the glyoxylate shunt enzyme isocitrate lyase

Abstract: Mycobacterium tuberculosis claims more human lives each year than any other bacterial pathogen. Infection is maintained in spite of acquired immunity and resists eradication by antimicrobials. Despite an urgent need for new therapies targeting persistent bacteria, our knowledge of bacterial metabolism throughout the course of infection remains rudimentary. Here we report that persistence of M. tuberculosis in mice is facilitated by isocitrate lyase (ICL), an enzyme essential for the metabolism of fatty acids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
986
7
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,225 publications
(1,066 citation statements)
references
References 22 publications
50
986
7
9
Order By: Relevance
“…Genes associated with DNA repair such as end (coding for a probable endonuclease) and recA (encoding recombinase A 26 ) were up-regulated; together with Rv3049c (a probable monoxygenase) and aphC (alkyl hydroperoxide reductase) expressed in response to oxidative stress 27 . Also over-expressed after drug treatment (>3 drugs) were gltA1 (a probable citrate synthase) and icl (isocitrate lyase) similar to changes in metabolism seen under stress conditions 28 . RNA polymerase sigma factors A and B were also induced, together with serine/threonine protein kinases B and G. sigB has been implicated in the M. tuberculosis response to a number of stress conditions 29 .…”
Section: Microarray Data Analysismentioning
confidence: 78%
“…Genes associated with DNA repair such as end (coding for a probable endonuclease) and recA (encoding recombinase A 26 ) were up-regulated; together with Rv3049c (a probable monoxygenase) and aphC (alkyl hydroperoxide reductase) expressed in response to oxidative stress 27 . Also over-expressed after drug treatment (>3 drugs) were gltA1 (a probable citrate synthase) and icl (isocitrate lyase) similar to changes in metabolism seen under stress conditions 28 . RNA polymerase sigma factors A and B were also induced, together with serine/threonine protein kinases B and G. sigB has been implicated in the M. tuberculosis response to a number of stress conditions 29 .…”
Section: Microarray Data Analysismentioning
confidence: 78%
“…Supporting this, it has been shown that survival of Mycobacterium tuberculosis in hypoxic conditions is reduced when pathogen-derived succinate production is inhibited [38], suggesting that this metabolite is required for cell viability. Furthermore, compared to levels in resting macrophages, ICL activity was increased in M. tuberculosis-infected macrophages following activation with LPS [39], suggesting that LPS stimulation may increase the activity of this enzyme and therefore the production of succinate. Interestingly, whereas particular TCA cycle intermediates including succinate are elevated in macrophages following LPS stimulation, isocitrate and IDH are significantly decreased.…”
Section: Factors Contributing To Succinate Accumulationmentioning
confidence: 92%
“…This has enabled dissection of the enzymatic apparatus in response to altered environmental conditions. Altered genes include sigma factors [39,40] and PGRS-encoding genes [41], as well as activation of alternative pathways in the citrate cycle to allow metabolism of the abundant lipids in the necrotic centre of granulomas [42,43] and general adaptation to low oxygen tension [44]. More recently, in vitro studies identified a regulon consisting of two sensor kinases, DosS and DosT, under the control of the transcription factor DosR, which sense and control the host response to hypoxia and nitric oxide stress [45][46][47], thus enabling M. tuberculosis to adapt to local conditions during latency [48] (Figure 5).…”
Section: Transition Of M Tuberculosis Into a Dormant State Within Grmentioning
confidence: 99%